2019
DOI: 10.1002/cam4.2614
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐ion radiotherapy combined with chemotherapy for head and neck mucosal melanoma: Prospective observational study

Abstract: This study aimed to evaluate the efficacy of carbon‐ion radiotherapy in combination with chemotherapy using dacarbazine, nimustine, and vincristine (DAV therapy) in mucosal melanoma. Twenty‐one patients with clinically localized mucosal melanoma of the head and neck were enrolled. The primary endpoint was 3‐year overall survival (OS). Secondary endpoints included local control, progression‐free survival (PFS), and adverse event occurrence. Carbon‐ion radiotherapy with a dose of 57.6‐64.0 Gy (relative biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Koto et al suggested that concurrent chemotherapy was a markedly independent factor for OS, 26 similar to results of concurrent chemo‐RT in patients with inoperable locally advanced nonsmall cell lung cancer 28 . A recent study by Takayasu et al may have included the same patients as Shirai et al, therefore the former publication was not included in this review 29 . They suggested that efficacy of DAV therapy combined with CIRT increased survival rates, 29 however, also opposite results were reported 30 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Koto et al suggested that concurrent chemotherapy was a markedly independent factor for OS, 26 similar to results of concurrent chemo‐RT in patients with inoperable locally advanced nonsmall cell lung cancer 28 . A recent study by Takayasu et al may have included the same patients as Shirai et al, therefore the former publication was not included in this review 29 . They suggested that efficacy of DAV therapy combined with CIRT increased survival rates, 29 however, also opposite results were reported 30 .…”
Section: Discussionmentioning
confidence: 96%
“…A recent study by Takayasu et al may have included the same patients as Shirai et al, therefore the former publication was not included in this review 29 . They suggested that efficacy of DAV therapy combined with CIRT increased survival rates, 29 however, also opposite results were reported 30 . The patients included in the Shirai et al study were as well included in that of Koto et al; thus, further studies with larger sample sizes are required to determine whether concurrent chemotherapy is a predictor of OS rates.…”
Section: Discussionmentioning
confidence: 99%
“…The CIRT has been used to treat several tumors of the head and neck area. It has not been employed for squamocellular carcinoma-the most common entity-but rather, for other, radioresistant histologies, such as salivary gland tumors [15][16][17][18][19][20][21][22], paranasal sinuses tumors (including sinonasal undifferentiated carcinoma, sinonasal adenocarcinoma, intestinal-type adenocarcinoma, and esthesioneuroblastoma, among others) [15,23], mucosal melanoma [24][25][26][27][28], lacrimal gland tumors [29][30][31], and bone and soft tissue sarcoma (including tumors of the skull base and cervical spine [32][33][34][35][36][37][38] At MedAustron, CIRT was begun in July 2019. Until September 2020, 91 patients have been treated and 42 of them had tumors in the head and neck.…”
Section: Cirt Protocols For Head and Neck In Medaustronmentioning
confidence: 99%
“…Takayasu and colleagues [ 81 ] at Gunma University conducted a prospective observational study of combination CIRT with dacarbazine, nimustine, and vancristine for MM. Twenty-one patients with T4a or T4b rhinosinus disease were treated with CIRT to 57.6 to 64.0 GyRBE in 16 fractions, with 2 to 3 cycles of adjuvant dacarbazine, nimustine, and vancristine.…”
Section: Mucosal Melanomamentioning
confidence: 99%
“…Distant failure occurred in 52% of patients. No patients developed grade 3 or higher toxicity [ 81 ].…”
Section: Mucosal Melanomamentioning
confidence: 99%